DAKWAH TERAUPETIK DI SOSIAL MEDIA SEBAGAI UPAYA PREVENTIF TERHADAP COPYCAT SUICIDE PADA GEN Z - Reyza, Fadilla Arfa; Muhammad Baharuddin Iqbal; Mochammad Nasrullah (UIN Sunan Kalijaga Yogyakarta, 2025)
The phenomenon of copycat suicide—suicidal behavior triggered by exposure to information or news about similar cases—has become increasingly concerning, particularly among Generation Z, who are highly active on digital platforms. This vulnerability is influenced by psychological, social, and cultural factors, including communication patterns prevalent in social media. Therefore, a da’wah approach that is not only informative but also therapeutic and relevant to the characteristics of this generation is essential. This study aims to examine preventive efforts to reduce the occurrence of copycat suicide among Generation Z. The research employed a descriptive qualitative method with a literature review approach. The findings reveal that delivering therapeutic da’wah to Generation Z requires consideration of their psychological traits, which favor simple communication, concise messages, and visual content. The da’wah material may include the interpretation of Qur’anic verses containing motivational messages, the understanding that meditation can be practiced through prayer (shalat), and the introduction of relaxation techniques through dhikr and supplication (du’a). This approach is expected to enhance the psychological resilience of Generation Z and prevent the occurrence of copycat suicide. Keywords: Da’wah, Therapeutic, Copycat Suicide, Gen Z.